(untitled) (Memorandum: Memória e História em Psicologia, 2003)
This paper aims at investigating the presence of psychological literature in Konrad Lorenz’s work as a preliminary instrument to investigate how Lorenz’s ideas are related to Psychology. The bibliography of fourteen books written by Konrad Lorenz (including three volumes containing 26 selected papers) have been analyzed. A total of 245 references related to Psychology and related sciences have been selected. These references were organized in five groups: a) The pioneers of Ethology; b) Animal and Comparative Psychology; c) General Psychology (Associationism, Structuralism, Functionalism, Russian Reflexology and Classic Conditioning, Perceptual and Gestalt Psychology, Psychoanalysis, Behaviorism, Social and Developmental Psychology, Cognition, Emotion and Motivation); d) Epistemology; e) Psychiatry and Neurosciences. These data show that the History of Ethology and, particularly, Lorenz’s ideas, show an extremely important relation with Psychology, justifying the inclusion of Konrad Lorenz also in the History of Psychology.